2018
DOI: 10.1016/j.isci.2018.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Aβ Oligomers Impair Dipolar Heterodendritic Plasticity by Activation of mGluR in the Hippocampal CA1 Region

Abstract: SummarySoluble Aβ oligomers (oAβs) contribute importantly to synaptotoxicity in Alzheimer disease (AD), but the mechanisms related to heterogeneity of synaptic functions at local circuits remain elusive. Nearly all studies of the effects of oAβs on hippocampal synaptic plasticity have only examined homosynaptic plasticity. Here we stimulated the Schaffer collaterals and then simultaneously recorded in stratum radiatum (apical dendrites) and stratum oriens (basal dendrites) of CA1 neurons. We found that the api… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 69 publications
(88 reference statements)
3
7
0
Order By: Relevance
“…Application of [AβS26C] 2 had no detectable impact on paired-pulse facilitation (fig. S5), as expected (18, 24, 28). An alternative hypothesis was inspired by reports on an Aβ-dependent defect of the glutamate homeostasis, possibly involving an impairment of glutamate reuptake (1820).…”
Section: Hyperactivation Through An Aβ-dependent Block Of Glutamate Rsupporting
confidence: 85%
“…Application of [AβS26C] 2 had no detectable impact on paired-pulse facilitation (fig. S5), as expected (18, 24, 28). An alternative hypothesis was inspired by reports on an Aβ-dependent defect of the glutamate homeostasis, possibly involving an impairment of glutamate reuptake (1820).…”
Section: Hyperactivation Through An Aβ-dependent Block Of Glutamate Rsupporting
confidence: 85%
“…Moreover, the susceptibility of LTP at the different synaptic inputs to disruption by Aß varies. Thus, we (Hu et al, 2009) and others (Zhao et al, 2018) found that NMDA receptor-dependent LTP at basal synapses, unlike apical synapses, is resistant to inhibition by exogenously applied Aß.…”
Section: Resultsmentioning
confidence: 52%
“…In several mouse models of AD, social learning and responses are impaired at an early stage, often prior to overt spatial memory defects [113117] suggesting that overt disruptions in the CA2-SO circuit precede those within the CA3-CA1 SR Schaffer collateral circuit in AD. This may reflect early selective changes within the CA2-SO circuit which suppress signal propagation and PTP [118] through this hippocampal subfield, such as increased expression of inhibitory GABA Aα2, α5, [119] and K ATP channel subunits, as well as GFAP [120]. In addition to upregulated inhibitory mediators within the SO, alternative compensatory mechanisms may be recruited concurrently within the CA3-CA1 SR synapse which augment synaptic signaling, such as increased nNOS and NO [29].…”
Section: Discussionmentioning
confidence: 99%
“…Additional pathogenic Ca 2+ -mediated features that are well-characterized in 3xTg-AD mice are also detailed in other AD mouse models. For example, increased Ca 2+ -activated K + channel activity driven by upregulated RyR-Ca 2+ [28] is verified in the TgCRND8 model along with its effects on neurotransmission and neuronal excitability [118, 119]. The increase in the frequency of spontaneous neurotransmitter vesicle release at the CA3-CA1 synapse has been replicated in two additional lines of AD mice [59, 113].…”
Section: Discussionmentioning
confidence: 99%